2019
DOI: 10.4186/ej.2019.23.6.501
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Local Knowledge in Adaptation to Landslide Disasters in Sri Lanka

Abstract: Natural disasters are unforeseen events which occur at hydrologic, geologic, and atmospheric origins. The Policy-makers still rely on mitigation strategies based on scientific approaches. However, many scholars had emphasized the importance of incorporating local knowledge and related practices for disaster risk management. In that context, this study investigates the local knowledge in adaptation to mitigate the landslides disaster situations by studying a village in Sri Lanka which is located at the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The particular order and dimensions of IK can be identified in the Banyumas community, including their landslide mitigation strategies. Similar to previous findings in [22,91], with an agricultural community setting that develops local awareness, modified farming design, and traditional EWS, the Banyumas people have integrated their local values and beliefs into practical solutions [44]. As mentioned in Syahputra [19], the study also noted that less understanding of the knowledge had become one of the significant factors that decreased IK.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The particular order and dimensions of IK can be identified in the Banyumas community, including their landslide mitigation strategies. Similar to previous findings in [22,91], with an agricultural community setting that develops local awareness, modified farming design, and traditional EWS, the Banyumas people have integrated their local values and beliefs into practical solutions [44]. As mentioned in Syahputra [19], the study also noted that less understanding of the knowledge had become one of the significant factors that decreased IK.…”
Section: Discussionsupporting
confidence: 82%
“…The previous study in Sri Lanka has identified the local knowledge of landslide mitigation practices of remote communities through establishing early warning indicators, promoting warning systems, practicing collective farming, and optimizing the vegetation for fences and stone walls [22,39]. In that last article, focus group discussions, household surveys, and interviews were employed to evaluate local knowledge as a major part of the communities' social capital.…”
Section: Local Mitigation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It becomes the foundation of all environmental solutions for problems related to agriculture, the health care sector, food preparation, natural resource management, education, etc (Berkes 2009;Hiwasaki et al 2014;Islam et al 2018;Lin & Chang 2020). In addition, local knowledge plays an essential role in contributing the basic techniques and strategies by providing early warning systems and weather forecasting management for disaster risk reduction (Dasanayaka & Matsuda 2019;Hiwasaki et al 2014).…”
Section: Introductionmentioning
confidence: 99%